PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA, DISIPLIN KERJA DAN IKLIM KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERUMAHAN, KAWASAN PERMUKIMAN DAN PERTANAHAN KOTA DENPASAR - Ni Luh Made Yuni Pradnyawati; Nengah Landra; Ida Bagus Made Widiadnyana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
Performance is a concept that shows the relationship between work performance and the time unit needed to produce certain products and services from a workforce. The success of employee performance will directly shape the success of the organization. This study aims to test and obtain empirical evidence of the effect of human resource development, work discipline and work climate on employee performance at The Housing Office of Residential Area and Land of Denpasar City. The population of this research is 92 peoples. Sampling in this study using a saturated sampling technique (total sampling) where the entire population is a sample. This research was conducted at The Housing Office of Residential Area and Land of Denpasar City . The data was collected through a questionnaire. The analysis technique used is the instrument test, classical assumption test and multiple linear regression. The results showed that human resource development, work discipline and work climate had a positive and significant effect on employee performance at The Housing Office of Residential Area and Land of Denpasar City.